The role of the financial supervision authority and the situation of the client on the financial services market with special emphasis on the banking services market - Rutkowska-Tomaszewska, Edyta (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
A well-functioning financial services market should be stable and transparent, as well as ensure security and protect the interests of its participants. These goals and tasks are defined in a number of legal acts, and an important role in their realization has been entrusted to the Polish Financial Supervision Authority as the oversight body for the financial services market. The Polish Financial Supervision Authority (hereinafter referred to as the FSA) has been equipped with tools allowing it to counteract impermissible actions of financial services market participants, such as entities subject to oversight due to their provisioning of financial services. Within the scope of its oversight, the Financial Supervision Authority examines whether the interests of market participants and their security have been violated. It is also equipped with the capacity to undertake actions of a direct nature – operating on the basis of competences granted to it by particular regulations concerning its tasks, or also indirectly – in situations when it doesn’t have the standing to instigate the appropriate procedures, if it possesses information about violations and improprieties it can forward such information to authorized bodies in order to set in motion the relevant mechanisms.By performing its duties properly, the FSA can have a positive effect on the relationships between entities providing financial services and their clients, by restoring a semblance of balance and fairness.
Keywords: nadzór finansowy; rynek usług finansowych; rynek usług bankowych